2013
DOI: 10.12989/acc2013.1.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Engineering properties of steel fibre reinforced geopolymer concrete

Abstract: Engineering properties such as compressive strength, splitting tensile strength, modulus of rupture, modulus of elasticity and Poisson"s ratio of geopolymer concrete (GPC) and steel fibre reinforced geopolymer concrete (SFRGPC) have been obtained from standard tests and compared. A total of 15 specimens were tested for determining each property. The grade of concrete used was M 40. The percentages of steel fibres considered include 0.25%, 0.5%, 0.75% and 1%. In general, the addition of fibres improved the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…When fiber is induced, the elastic modulus can be affected mainly based on the fiber stiffness and porosity of the composite. For example, when a small quantity of steel fiber was used, up to 1 vol.%, the elastic modulus was slightly increased, which is correlated to the considerably high stiffness of steel and its strong fiber-binder interaction [114,167]. However, using up to 2 vol.% spiral steel and PP fibers, it was shown that the elastic modulus of steel fiber reinforced geopolymer concrete can be reduced or increased by a range of -18% to +16% of the plain sample.…”
Section: Elastic Modulus and Poisson's Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…When fiber is induced, the elastic modulus can be affected mainly based on the fiber stiffness and porosity of the composite. For example, when a small quantity of steel fiber was used, up to 1 vol.%, the elastic modulus was slightly increased, which is correlated to the considerably high stiffness of steel and its strong fiber-binder interaction [114,167]. However, using up to 2 vol.% spiral steel and PP fibers, it was shown that the elastic modulus of steel fiber reinforced geopolymer concrete can be reduced or increased by a range of -18% to +16% of the plain sample.…”
Section: Elastic Modulus and Poisson's Ratiomentioning
confidence: 99%
“…9. a) Elastic modulus and b) Poisson's ratio to the compressive strength of geopolymer composites. Adapted from Refs [74,114,130,136,138,167,197,[205][206][207][208][209]…”
mentioning
confidence: 99%
“…The measured value of Poisson ratio ranged between 0.200 and 0.189. Plain concrete had a Poisson ratio of 0.1995, for normal strength concrete, a value of 0.2 is usually adopted [42]. While SFRC shows a slight decrease in Poisson ratio as the fiber content increased.…”
Section: Fig (9) Poisson Ratio Of Sfrcmentioning
confidence: 99%
“…In a hybrid fibre combination, the microfibres bridge the microcracks, whereas the macrofibres are more efficient in controlling the development of macrocracks in the concrete [14][15][16][17]. Geopolymer behaves comparably to conventional cement binders; hence the hybrid fibres can also be incorporated in geopolymer concrete to improve the mechanical properties [18][19][20][21][22][23]. Many researchers carried out many investigations on the properties of fibre reinforced unary and binary blend geopolymer concrete in the past [24,25].…”
Section: Introductionmentioning
confidence: 99%